Successful Endoscopic Removal of a Lighter Swallowed 17 Months Before - Gorana Trgo; Ante Tonkic; Miroslav Šimunic; Željko Puljiz (Case Reports in Gastroenterology, 2012)
The majority of ingested foreign bodies will pass safely through the gastrointestinal tract, but long and rigid foreign bodies are associated with an increased risk of gastrointestinal impaction, perforation and bleeding. However, large foreign bodies which have been swallowed can remain trapped in the stomach over a longer period of time without any significant symptoms. This case report describes the case of a 36-year-old man addicted to heroin who purposefully swallowed a lighter (double wrapped in cellophane) and presented with hematemesis and melena 17 months after the ingestion of the foreign body. The lighter was successfully removed via flexible endoscopy using a polypectomy snare. Swallowed long and rigid foreign bodies trapped in the stomach over a long period of time always represent a special clinical and endoscopic challenge. In cases where endoscopic removal fails, a laparoscopic surgical approach may be an alternative.